2006
DOI: 10.1097/01.sla.0000205827.73706.97
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Extrahepatic Portal Vein Thrombosis by the Mesenteric to Left Portal Vein Bypass

Abstract: MLPVB provides excellent relief of symptoms in children with idiopathic EHPVT and results in liver growth and normalization of coagulation parameters. This surgery is corrective and should be done at as early an age as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
116
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 20 publications
8
116
0
6
Order By: Relevance
“…Therefore, its efficiency is very limited and the mortality rate due to gastric bleeding is high [13] . The application of surgical treatment is limited by tissue damage and additional complications [14][15][16][17] . With the development of interventional radiology, minimally invasive technology has become one of the predominant means of treating acute-subacute PV-SMV thrombosis without obvious intestinal necrosis, perforation, and peritonitis [18][19][20][21][22][23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its efficiency is very limited and the mortality rate due to gastric bleeding is high [13] . The application of surgical treatment is limited by tissue damage and additional complications [14][15][16][17] . With the development of interventional radiology, minimally invasive technology has become one of the predominant means of treating acute-subacute PV-SMV thrombosis without obvious intestinal necrosis, perforation, and peritonitis [18][19][20][21][22][23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up results ranging between 1 and 7 years are available. In the largest study reported till date, 34 patients underwent this procedure with a success rate of 91%, good shunt patency rate, and rebleeding rate of 8% with amelioration of hypersplenism in most patients [59]. Although promising, long-term follow-up studies are needed to confirm its efficacy.…”
Section: Surgery For Secondary Prophylaxismentioning
confidence: 99%
“…Nonsurgical shunts such as TIPS have no role in EHPVO yet. The surgical options in EHPVO have been recently bolstered by the development of a new type of shunt, the mesenterico-left portal vein bypass (Rex shunt) in children [59]. This is a new paradigm in surgical treatment.…”
Section: Surgery For Secondary Prophylaxismentioning
confidence: 99%
“…The mesoportal bypass (MPB) is a recent advancement in shunt restoring mesenteric blood flow to the liver through the Rex venous recessus (interposition of a jugular venous allograft between the superior mesenteric vein and the intrahepatic left portal vein). This "Rex shunt" restores the physiological hepatopetal flow and thereby corrects the liver dysfunction, coagulation parameters and also improves the growth potential (Superina, 2006;Mack, 2003;Lautz, 2009). It appears that doing the Rex shunt early after diagnosis rather than waiting till complications will be beneficial.…”
Section: Surgical Management Of Ehpvomentioning
confidence: 99%
“…Although these shunts are effective in controlling variceal bleeding, encephalopathy is a concern in patients with poor liver functions. Follow up studies have shown shunt patency in 85-98% of children with long term survival in >95% cases (Lautz, 2009;Bismuth, 1980;Gauthier, 1989;Mitra, 1993;Prasad, 1994;Orloff, 1994;Superina, 2006;Shariff, 2010). Risk of variceal recurrence and rebleed is there in case of shunt blockage.…”
Section: Surgical Management Of Ehpvomentioning
confidence: 99%